Control biológico de larvas de la mosca del establo: Stomoxys calcitrans con el hongo entomopatógeno Metarhizium anisopliae in vitro - Bernal, Edgar; Arcila Quiceno, Victor Hernan; Serrano Novoa, Cesar Augusto (Spei Domus, 2005)
Due to extensive use of acaricides and insecticides in livestook industrie it has been developed a resistance phenomenom that generate the necesity to improve alternative methods for outter parasities control on cattle. Use of entomopathogenic fungus are available strategie. It has been executed checking labors about possible biocontrol effects of several kinds of fungus but these tests are focused on Boophilus microplus. This is a first step in the development of an in vitro methodology to evaluate a biological control starting from second instar larvaes of Stomoxys calcitrans with the entomopathogenic fungus Metarhiziumanisopliae. Four stocks were evaluated: the first stock was applied with a concentration of 1x102conidia/ml, 1x104 conidia/ml, 1x106 conidia/ml and 1x108 conidia/ml of M.anisopliae. They were maintained under laboratory conditions at 23 °C and 80% relative humidity. Three isolation were applied with a concentration of 1x107 conidia/mlof M. anisopliae. They were maintained under laboratory conditions at 18 °C and 63% relative humidity. The total mortality produced by each tack was checked. None of the four stoks showed activity on the larvaes.